Neurotrauma Audit at Netaji Subhash Chandra Bose Medical College, Jabalpur, Madhya Pradesh - Kumar, Ambuj; Hedaoo, Ketan; Bajaj, Jitin; Sinha, Mallika; Ratre, Shailendra; Parihar, Vijay; Swamy, Narayan; Yadav, Y. R. (Indian Journal of Neurotrauma, 2019)
Introduction For the prevention and better management of traumatic brain and spine injury patients, it is mandatory to understand the demographic and clinical profiles of cases of a particular region. This study was aimed at describing the epidemiology, pattern, and outcomes of head and spine injury patients at a tertiary care center in central India.Materials and Methods All the patients with head and spine injury admitted to the Department of Neurosurgery between September 1, 2018, and August 31, 2019 were included in the study. Data of all these patients were collected from the medical record section and analyzed for age, sex, mode of injury, severity of injury, management, and outcomes.Results During the study period, 932 patients with head injury and 241 patients with spine injury were admitted to our department. Around 65% of the patients in both head and spine injury categories fell in the age group of 26 to 55 years. Approximately 80% of all neurotrauma patients were male. The most common mode of injury was road traffic accident followed by fall from height. Mortality for severe head injury was 39% and that for ASIA A (American Spinal Injury Association grade A) cervical spine injury was 65%.Conclusion Even after aggressive treatment strategies, morbidity and mortality are very high, and the ultimate outcome depends mainly on the clinical status immediately after trauma. The data from this study can be helpful in strategy-making for the prevention and management of head and spine injury patients, especially in the central Indian population.
Keywords: neurotrauma audit; head injury; morbidity; mortality; neurotrauma; spine injury